2019
DOI: 10.3389/fpls.2019.00671
|View full text |Cite
|
Sign up to set email alerts
|

Silicon Supplementation of Rescuegrass Reduces Herbivory by a Grasshopper

Abstract: The theory of coevolution suggests that herbivores play an important role in the diversification and composition of plant communities. A prevalent idea holds that grasses and grazing animals participated in an evolutionary “arms race” as grassland ecosystems started spreading across the continents. In this race, besides other things, silicification in the form of phytoliths occurred in the grasses, and the graminivorous herbivores responded through specialized mandibles to feed on plants rich in phytoliths. It… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
10
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 25 publications
(12 citation statements)
references
References 53 publications
1
10
1
Order By: Relevance
“…A previous study showed that a c. 15% increase in Si concentration significantly reduced grasshopper herbivory in rescuegrass Bromus catharticus, albeit this reduction in herbivory occurred even at Si concentrations substantially lower than this study (Mir et al, 2019). Our findings suggest that Si might be a particularly effective defence as it can be deployed very rapidly, in a matter of hours, but once deposited as silica-rich structures such as phytoliths, it is also known to remain in tissues and serve as an effective herbivore defence for, at least, many months (Epstein, 1994;Reynolds et al, 2012).…”
Section: Si Accumulation Is a Rapidly Induced Defencecontrasting
confidence: 76%
“…A previous study showed that a c. 15% increase in Si concentration significantly reduced grasshopper herbivory in rescuegrass Bromus catharticus, albeit this reduction in herbivory occurred even at Si concentrations substantially lower than this study (Mir et al, 2019). Our findings suggest that Si might be a particularly effective defence as it can be deployed very rapidly, in a matter of hours, but once deposited as silica-rich structures such as phytoliths, it is also known to remain in tissues and serve as an effective herbivore defence for, at least, many months (Epstein, 1994;Reynolds et al, 2012).…”
Section: Si Accumulation Is a Rapidly Induced Defencecontrasting
confidence: 76%
“…Previous studies have shown that Si has a negative effect on H. armigera growth [6,27]. Orthopterans also respond negatively to Si [12], but are not affected to the same extent as lepidopterans [23]. The significantly reduced frass collected from both insects on Si+ plants suggests that Si is acting as a feeding deterrent.…”
Section: Discussionmentioning
confidence: 82%
“…These Si-induced changes in leaf surface morphology are particularly effective against insect herbivores, reducing leaf consumption and hindering digestion [9,10]. Silica cell density in the leaf epidermis generally increases with Si availability, leading to tougher and more abrasive leaves and decreased herbivore performance [11,12]. Si can also be deposited in other surface structures such as trichomes, increasing their length and density [11,13].…”
Section: Introductionmentioning
confidence: 99%
“…Structural rigidity and toughness in plants depends on lignification, as well as re‐enforcement by minerals from soils, such as silicic acid (Si[OH] 4 ) deposited as amorphous silicon dioxide (SiO 2 ) in epidermal phytoliths, spines and trichomes of plants (Hartley, Fitt, McLamon, & Wade, 2015; Ma, 2004). Addition of silicon to soil significantly reduced grasshopper damage in rescuegrass (Mir et al, 2019), and diminished stem boring damage by the Asiatic rice borer Chilo suppressalis (Hou & Han, 2010). Interestingly, deficiency in the silicon transporter Lsi1 compromised the inducibility of antiherbivore defense in rice, suggesting involvement of Si in regulation of defense responses (Lin et al, 2019).…”
Section: Discussionmentioning
confidence: 99%